Danilo Cruz Vélez y la superación de la metafísica de la subjetividad (2015)
Danilo Cruz Vélez appreciates the attempt made by Edmund Husserl to free the philosophy from all suppositions, specifically for everyday belief in the existence of the world, also known as a general thesis of the natural attitude. For Edmund Husserl, the starting point of philosophy is the negation of that thesis, epojé, allowing the return of self to self erecting, as it as done by René Descartes methodical doubt of centuries ago, as the only true in which you can substantiate everything. It is the latter that precisely Danilo Cruz Vélez more criticism, that the father of phenomenology did not realize the main course which was still submerged: the metaphysics of subjectivity. Hence the caldense philosopher expose the thought of his teacher, Martin Heidegger, who did not despise the natural attitude, but who rated it as a starting point for philosophizing. From this difference, according to Danilo Cruz Vélez, the philosopher of the Black Forest was able to overcome the metaphysics of subjectivity, by not using the concept of representation, so linked to sight but to propose the concept of use of, forgive the repetition, useful, more connected to the hand. The question is: Martin Heidegger managed to get really, of the metaphysics of subjectivity?